BASIN GEOMETRY ANALYSIS OF “NOKEN” AREA, MESOZOIC INTERVAL, AKIMEUGAH BASIN, PAPUA - David Ontosari; Benyamin Sapiie; Hermes Panggabean; Edy Slameto (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2018)
Area